2013
DOI: 10.1590/s1519-69842013000300027
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic characteristics of the cattle egret Bubulcus ibis (Linnaeus, 1758) in the Brazilian semiarid

Abstract: Cattle egret Bubulcus ibis (Linnaeus, 1758) is a highly synanthropic species, which has been benefitted by the increase of livestock in recent decades (Sick, 1997). The species originates from the Old World and spread to all the continents, with the exception of Antarctica (Martínez-Vilalta and Moltis, 1992). Three current concerns of this expansion and population growth are: competition for resources or predation of endemic species (Barbosa-Filho et al., 2009), transmission of diseases to the human population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…From the point of view of animal health, cattle egrets habitually come into close proximity to cattle, sheep, goats and horses, 6 , 7 which suggests that they may serve as sources of infection for humans and livestock. 5 , 6 Several authors have suggested that contact between synanthropic birds and poultry production units might be a transmission route for Salmonella to poultry species and consequently to their carcasses. 24 , 31 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the point of view of animal health, cattle egrets habitually come into close proximity to cattle, sheep, goats and horses, 6 , 7 which suggests that they may serve as sources of infection for humans and livestock. 5 , 6 Several authors have suggested that contact between synanthropic birds and poultry production units might be a transmission route for Salmonella to poultry species and consequently to their carcasses. 24 , 31 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Although the most native marine birds of Fernando de Noronha are not endangered species, infected cattle egrets may have a negative impact through transmission of Salmonella to these species. Through competition for ecological niches with native species, presence of cattle egrets may thus increase the mortality rates among the local avifauna 2 , 5 , 6 if the Salmonella serovars that they carry happen to cause disease outbreaks in the local populations of wild birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation